Associação de polimorfismos únicos de nucleotídeos de genes de citocinas com a esclerose múltipla - Cadidé, Renata Campos (2014)
Multiple sclerosis (MS) is a multifactorial autoimmune disease characterized by inflammation in the central nervous system (CNS). In this disease the proteins that form the myelin sheath are considered one of the main targets of degeneration and its impairment can cause disorders in synaptic transmission followed by functional impairment. This work aimed to perform an association study of genetic markers of cytokines between patients and a group control of healthy individuals. Samples were collected from 82 patients with MS, assisted by the Reference Center for Demyelinating Diseases of the Hospital of the State University of Londrina (Paraná, Brazil) and 170 healthy controls, not related. The genotyping of cytokines wasdetermined by method PCR-SSP (Polymerase Chain Reaction- Sequence Specific Primer) using commercial kit (Cytokine Genotyping Kit, Invitrogen ).There were significant differences in the frequencies of alleles, genotypes and haplotypes of cytokines between cases and controls.Was assigned significant influence, the following polymorphic variants in genes of proinflammatory cytokinesTNFA-308, -238 (GG/GA, GA/AA and GG/AG) -238 (G/G, A/A, G and A) -308 (G/G), IL6-174,nt565(GG/CG) nt565 (G/G and G) andanti-inflammatory IL4RA+1902(A/A, A and G)andIL10-1082, -819, -592(GCC/ATA and ACC/ACC).The results suggest that single base mutations in genes for cytokines and cytokine receptors potential determinants are predisposed to MS. Such evidence may assist in understanding the etiology of MS, both for innovations in research on genetic markers associated with the disease, and for the development of procedures that can minimize their impacts (social and individual) through strategies in the prevention, diagnosis, genetic counseling and treatment.